A new species of Palaemon (Crustacea, Decapoda, Palaemonidae) from Qatar - de Grave, S.; Al-Maslamani, I. (Zootaxa, 2006)
A new species of palaemonid shrimp, Palaemon khori sp. nov. is described from Qatar. The new species is closely related to Palaemon debilis Dana, but can be distinguished from that species by its rostral shape, the near quadrate fifth pleuron, a wider and less elongate telson, longer mesial telson spines, as well as details of the male first and second pleopods. A number of other morphological features are recorded here for the first time in a species of Palaemon, notably the marginal setation of the distal half of the telson.